Characterization and performance evaluation of zinc oxide varistor blocks processed by latex binders - Begum, Shahida Nathira; Karim, A.N. Mustafizul; Hashmi, M. S. J. (Blackwell Publishing, 2008)
The processing of ZnO varistor has a long route with numerous contributing variables. The binder plays an important role in the fabrication of this electro-ceramic device. Higher density and strength of a green body are critical not only for handling at its green state but also to avoid the causes of flaw formation during sintering. Use of appropriate binder can lead to improved characteristics of powder, which will reduce density gradient in the green body during compaction. Enhanced green properties can consequently lead to higher fired strength of the varistor discs. The binder system is anticipated to have an influence on the grain growth and microstructure which in turn affect the electrical performance parameters of the discs such as I-V characteristics, watt-loss behavior, and energy absorption capability, etc. To investigate this phenomenon, several commercial latex binders and their blends have been studied and compared with the conventional plasticized polyvinyl alcohol. A positive effect was observed in the context of physical properties and electrical performance of ZnO varistors. Factorial analysis has revealed that the two input parameters (binder content and solid concentration) influence the electrical properties such as electric field intensity, non-linear co-efficient, energy absorption capability, and watt-loss of ZnO varistor.